Front and rear suspension design for solar car - Mohd Dzohairy, Mohammad Mohsan (2010)
Suspension is a necessary system for solar cars because it protects the frame and other on-board components from large jolts encountered along highways. If the suspension is too soft, energy is wasted by absorbing the motion of a car as it travels over bumps. For increased efficiency, most solar cars use a suspension that is stiffer than normal. For this project, the solar car has two front wheels and one rear wheel. The front wheels provide turning, so the front suspension needs to let the wheels turn. The suspension also allows the wheels to move up and down as the car runs over bumps. The type of front suspension for this project is a double wishbone system. It has a pair of an A-frames, one above the other, mounted to the top and bottom of the wheel hub. A separate spring until then sits between either the hub itself or one of the wishbones and the body to control the wheel movement. Lastly, this car uses a trailing arm on rear suspension. This kind of suspension has only one link (arm) on each side which puts greater structural requirements on it. Strong bending forces in all directions (especially during cornering) must be withstood by this suspension and as well as breaking, camber and steer torques. Nevertheless trailing arm suspension has been used in many vehicles as a rear linkage, because it requires little space to be accommodated